Two-phase natural convection dusty nanofluid flow. (March 2018) - Siddiqa, Sadia; Begum, Naheed; Hossain, M.A.; Gorla, Rama Subba Reddy; Al-Rashed, Abdullah A.A.A.
Highlights: In this paper behavior of nanofluid is discussed in detail for two-phase dusty model. The solutions are obtained through finite difference scheme. The effects of the parameters on skin friction coefficient, rate of heat and mass transfer are explored. It is concluded that the NA and NB has pronounced effect in reduction of heat transfer rate. Abstract: An analysis is performed to study the two-phase natural convection flow of nanofluid along a vertical wavy surface. The model includes equations expressing conservation of total mass, momentum and thermal energy for two-phase nanofluid. Primitive variable formulations (PVF) are used to transform the dimensionless boundary layer equations into a convenient coordinate system and the resulting equations are integrated numerically via implicit finite difference iterative scheme. The effect of controlling parameters on the dimensionless quantities such as skin friction coefficient, rate of heat transfer and rate of mass transfer is explored. It is concluded from the present analysis, that the diffusivity ratio parameter, N A and particle-density increment number, N B have pronounced influence on the reduction of heat transfer rate.